2003
DOI: 10.1590/s1517-83822003000400008
|View full text |Cite
|
Sign up to set email alerts
|

Activity of glucose-fructose oxidoreductase in fresh and permeabilised cells of Zymomonas mobilis grown in different glucose concentrations

Abstract: Previously grown cells of the ethanologenic bacterium Zymomonas mobilis produce sorbitol and gluconic acid, in reactions catalysed by the periplasmic enzymes glucose-fructose oxidoreductase (GFOR) and glucono-δ-lactonase (GL). The GFOR/GL system activity, in cells to be used in this bioconversion, depends on growth conditions. In batch runs, with initial glucose concentrations (S0) from 42 to 230 g/L, the highest specific and total GFOR/GL activities were obtained with S0 = 153 g/L (12.6 U/g cells and 62 U/L).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…This influence had already been reported by Zachariou and Scopes [24]. In that study, the authors showed that the highest activity of GFOR was obtained when a high glucose concentration was added to a However, glucose concentrations [150 g l -1 cause an inhibition of the cellular growth [8].…”
Section: Evaluation Of the Cultivation Mediumsupporting
confidence: 69%
See 1 more Smart Citation
“…This influence had already been reported by Zachariou and Scopes [24]. In that study, the authors showed that the highest activity of GFOR was obtained when a high glucose concentration was added to a However, glucose concentrations [150 g l -1 cause an inhibition of the cellular growth [8].…”
Section: Evaluation Of the Cultivation Mediumsupporting
confidence: 69%
“…Both rich and defined composition media were prepared. Media containing glucose concentrations [150 g l -1 were not used because of the known substrate inhibition at high sugar concentrations [8].…”
Section: Microorganism and Maintenancementioning
confidence: 99%
“…Other uses include vitamin C, sorbose, glycerol propylene, plastics and resin production. Sorbitol can be used in dietetic foods for diabetics because it is not insulindependent (6,17).…”
Section: Introductionmentioning
confidence: 99%
“…After the catalytic hydrogenation process, the sorbitol is collected and purified, making the process expensive (6,8). However, other methods can be used to obtain sorbitol, such as the biotechnological process by fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…In these experimental runs, high concentrations of the substrate are used, since it consists of a more favorable condition to the action of the GFOR enzyme (Silveira et al 1999;Erzinger et al 2003). One can verify kinetic curves for the initial concentration of around 0.7 mol L −1 lactose and initial concentrations of around 0.35 mol L −1 Fig.…”
Section: Resultsmentioning
confidence: 93%